2021
DOI: 10.3390/ijerph18147571
|View full text |Cite
|
Sign up to set email alerts
|

How Capital Endowment and Ecological Cognition Affect Environment-Friendly Technology Adoption: A Case of Apple Farmers of Shandong Province, China

Abstract: Ever-increasing global environmental issues, land degradation, and groundwater contamination may significantly impact the agricultural sector of any country. The situation worsens while the global agricultural sectors are going through the unsustainable intensification of agricultural production powered by chemical fertilizers and pesticides. This trend leads the sector to exercise environmentally friendly technology (EFT). Capital endowment and ecological cognition may significantly impact fostering farmers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 73 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Existing studies on the factors influencing the adoption of EAT by farmers have found that farmers' intention to adopt is influenced by a combination of subjective and objective factors. Objective factors include social learning and social networks, socioeconomic factors, price factors, immediate conditions and social climate, green technology adoption risks and government regulation, the share of farmers' income in total household income and economic benefits of ecological production technologies, technological environment, plot elements and access to raw materials (Connor et al, 2021;Li et al, 2021;Ruzzante et al, 2021;Sapbamrer and Thammachai, 2021;Shang et al, 2021;Wang et al, 2021). The subjective factors are ecological compensation perception and ecological environment perception, ecological compensation intention, environmental crisis awareness, ecological environment improvement effect, and ecological environment policy perception (Savari et al, 2021;Tama et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on the factors influencing the adoption of EAT by farmers have found that farmers' intention to adopt is influenced by a combination of subjective and objective factors. Objective factors include social learning and social networks, socioeconomic factors, price factors, immediate conditions and social climate, green technology adoption risks and government regulation, the share of farmers' income in total household income and economic benefits of ecological production technologies, technological environment, plot elements and access to raw materials (Connor et al, 2021;Li et al, 2021;Ruzzante et al, 2021;Sapbamrer and Thammachai, 2021;Shang et al, 2021;Wang et al, 2021). The subjective factors are ecological compensation perception and ecological environment perception, ecological compensation intention, environmental crisis awareness, ecological environment improvement effect, and ecological environment policy perception (Savari et al, 2021;Tama et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To further enhance the efficiency of fertilizer utilization and improve the soil quality level and ecological environment of farmland, STFFT is gradually being promoted and accepted [ 13 , 14 ]. The proliferation of this technology has promoted agricultural carbon peaking and carbon neutrality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the control variables, the coefficient of years of education is significantly negative, indicating that farmers with higher years of education are less likely to overuse pesticides. Similarly, Cao et al ( 55 ) and Wang et al ( 56 ) found that farmers with higher education level are more likely to adopt environmentally friendly agricultural practices. The possible reason is that education can improve farmers' knowledge of pesticide use and have more advanced concepts, thereby reducing the possibility of overuse of pesticides.…”
Section: Resultsmentioning
confidence: 90%